Design and Analysis of Generic Energy Management Strategy for Controlling Second-Life Battery Systems in Stationary Applications - Mohamed Abdel-Monem; Omar Hegazy; Noshin Omar; Khiem Trad; Sven De Breucker; Peter Van Den Bossche; Joeri Van Mierlo (Energies, 2016)
Recently, second-life battery systems have received a growing interest as one of the most promising alternatives for decreasing the overall cost of the battery storage systems in stationary applications. The high-cost of batteries represents a prominent barrier for their use in traction and stationary applications. To make second-life batteries economically viable for stationary applications, an effective power-electronics converter should be selected as well. This converter should be supported by an energy management strategy (EMS), which is needed for controlling the power flow among the second-life battery modules based on their available capacity and performance. This article presents the design, analysis and implementation of a generic energy management strategy (GEMS). The proposed GEMS aims to control and distribute the load demand between battery storage systems under different load conditions and disturbances. This manuscript provides the experimental verification of the proposed management strategy. The results have demonstrated that the GEMS can robustly handle any level of performance inequality among the used-battery modules with the aim to integrate different levels (i.e., size, capacity, and chemistry type) of the second-life battery modules at the same time and in the same application.